Hypoxaemia associated with an enlarged aortic root: a new syndrome?. Issue 8 (10th March 2005) - Eicher, J-C; Bonniaud, P; Baudouin, N; Petit, A; Bertaux, G; Donal, E; Piéchaud, J F; David, M; Louis, P; Wolf, J E
Abstract : Objective: To assess the mechanisms through which an enlarged aortic root may facilitate right to left shunting through a patent foramen ovale. Patients: 19 patients with the platypnoea-orthodeoxia syndrome (POS) were compared with 30 control patients without platypnoea. Interventions: Multiplane transoesophageal echocardiography. Main outcome measures: The aortic root diameter, atrial septal dimension behind the aortic root, and amplitude of the phasic oscillation of the septum were measured. Four groups of patients were compared: 12 platypnoeic patients with a dilated aortic root (POS-D), 7 platypnoeic patients with a normal aortic root (POS-N), 15 control patients with a dilated aortic root (CONT-D), and 15 control patients with a normal aortic root (CONT-N). Results: In POS-D and CONT-D patients, the apparent atrial septal dimension was 16.3 (2.7) mm and 17.4 (5.9) mm respectively, compared with 24.4 (5.2) mm in POS-N patients and 25 (4) mm in CONT-N (p < 0.005). Furthermore, the amplitude of septal oscillation was 14.7 (2.5) mm in the POS-D group versus 5.8 (2.4) mm in CONT-N (p < 0.001) compared with 23.3 (3) mm in seven patients with an atrial septal aneurysm (p <0.001). Conclusion: Patients with an enlarged aorta have an apparently smaller dimension and increased mobility of the atrial septum. These findings appear to result from compression by the aortic root and decreased septal tautness. Consequently, a "spinnaker effect" with the inferior vena caval flow may take place, opening the foramen ovale and leading to sustained right to left shunting.